Implementation of the Child-Friendly City Program in Makassar City - Mardiana Tul; Lukman Hakim; Abdul Mahsyar; Fatmawati Fatmawati; Nuryanti Mustari (Universitas Sultan Ageng Tirtayasa, 2026)
A government initiative called the “child-friendly city initiative” reflects the integration of commitment and assistance across the government, community, and business sectors to ensure the implementation of the rights of children. This study is intended to examine how the child-friendly city program policy is being implemented in Makassar and to pinpoint the execution. This study is carried out utilizing a qualitative, descriptive approach, with interviews, observations, and file analysis conducted with informants from government agencies and other pertinent stakeholders involved in the execution of the child-friendly city initiative to collect data. The phases and stages that involve organizing data, displaying findings, and formulating conclusions were used to examine the data. This study found that the child-friendly city program in Makassar is implemented through various activities and policies to ensure the fulfillment of children's rights. These initiatives demonstrate the dedication of local governments and stakeholders to advancing child welfare. Nevertheless, several issues remain in the implementation process, including poor interagency collaboration, insufficient resources, and inadequate community involvement in program activities. These limitations affect the program’s overall efficacy. Therefore, to improve the efficacy and sustainability of the child-friendly city initiative in Makassar, it is imperative to develop cross-sector cooperation, enhance institutional capacity, and increase community engagement.